Research of transfer processes in liquids, their mixtures, in dense polyphase and biological media - Азнакаєв, Е. Г. (Proceedings of National Aviation University (archive), 1998)
Considered are in the theory of transfer processes in dense media with the account of one particle and multiple-particle movements. Proposed is the similarity law for balanced and unbalanced medium. Studied are the characteristics of turbulent flows